Analysis of Students' Difficulties in Solving Physics Problems Using Polya's Theory - Evendi; Mawarni Saputri; Haital Miza; Abdul Hamid (Postgraduate, University of Mataram, 2024)
The ability of students in solving physics problems used Polya's theory is still at a low level, in general students have difficulty in solving physics problems at the stages of planning and implementing problem solving. This study aims to determine the level of difficulty of students in solving physics problems used Polya's theory and find out what are the difficulties of students in solving physics problems used Polya's theory. The research approach used is mixed method, with the explanatory sequential design. Data collection techniques used tests and interviews. The results of data analysis show that the very high level of difficulty of students in solving equilibrium problems of rigid bodies is at the stage of seeing / checking back, but the difficulties experienced by students at this stage are very dependent on the other three stages of Polya, namely understanding the problem, planning problem solving and implementing problem solving. Students' difficulties in solving physics problems used Polya's theory, among others, students had difficulty in translating or changing the problem in physics symbols, students had difficulty in making plans because they did not know the formula that should be used, students had difficulty in completing mathematical operations and students did not re-examine the solution steps and answers that had been obtained so that some answers were still not correct.